Analisis Kualitas Layanan Self-Service terhadap Kepuasan Pelanggan di Restoran All You Can Eat Kota Bandung, Indonesia - Sundari Dwi Jayanti (Asosiasi Ahli Administrasi Indonesia, 2022)
This study aims to determine the effect of self-service quality on customer satisfaction at All You Can eat restaurants in Bandung. The method used in this research is descriptive quantitative method by collecting questionnaire data using Google Form to 100 people. The sampling technique used in this research is purposive sampling. The results showed that the functional variables (X1), enjoyment (X2), assurance (X3), and convenience (X4) had a significant influence on customer satisfaction at the All You Can Eat Restaurant in Bandung City.